The Influence of Segmental Psychological Guidance and Exercise on Narrative Psychology - Ting Yue (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Segmented psychological counselling and physical exercise exert a beneficial influence on narrative psychology, fostering enhanced comprehension and reconstruction of personal narratives among individuals. Consequently, this facilitates the advancement of psychological well-being and developmental processes. A retrospective analysis was undertaken to identify 50 young and middle-aged patients exhibiting mild depression. These patients were subsequently randomized into two groups: an observation group and a control group, each comprising 25 cases. The control group received standard medication treatment, while the observation group received additional psychological counselling and exercise alongside standard medication, mirroring the treatment protocol of the control group. Regarding self-esteem, anxiety, and depression, the participants in the experimental cohort demonstrated notable improvements following the intervention, suggesting that engagement in taekwondo sports can effectively enhance self-esteem and bolster the mental health status of middle school students. The novelty of the research lies in uncovering the combined influence of segmental psychological guidance and exercise on narrative psychology. This innovative approach provides a distinct method for fostering personal development and enhancing well-being by amalgamating cognitive and physical interventions. Implications and Taekwondo exercise demonstrates a greater efficacy in diminishing depression compared to anxiety among middle school students. Hence, the combination of segmental psychological counselling and exercise is more beneficial in alleviating depression levels and fostering students' willingness to engage in active psychological narration. Consequently, the utilization of segmental psychological guidance and exercise holds promise in enhancing the efficacy of narrative psychology towards facilitating personal growth and promoting well-being.